“You’re not the only one going through all them crazy changes”: Tracing Group Learning in Conversations - Deborah Kilgore (Adult Education Research Conference, 2002)
Conversation analysis is proposed as a means to uncover how group learning evolves via power negotiation among members. A case of oppositional learning within a prison is presented as an example.